Animal rights : current debates and new directions - Sunstein, Cass R.; Nussbaum, Martha C. (Martha Craven), 1947- (Oxford University Press, 2004)
Contributors to this volume explore the legal and political issues that underlie the campaign for animal rights and the opposition to it. Ethical questions on ownership, protection against suffering and the ability of animals to make their own choices free from human control are thought-provokingly examined.